PENINGKATAN SIKAP ILMIAH SISWA MELALUI PEMBELAJARAN BERBASIS PRAKTIKUM VIRTUAL INVERTEBRATA - Peny Husna Handayani; Fransisca Sudargo Tapilouw; Ana Ratna Wulan (Jurnal Pelita Pendidikan, 2018)
This study aims to analyze the students' scientific attitude improvement through virtual lab on invertebrates. The method that used was weak experimental design, with two classes of samples (X-7 and X-8) which has a parallel position as class treatment. The instrument that used for data collection was the scientific attitudes scale form of Likert scale. The results showed that the scientific attitudes improved significantly after virtual lab-based learning on invertebrates (sig-2tailed value <α (0.025)). Increased scientific attitude is low (N-Gain X-7 = 0.10, = 0.16 X-8). Virtual lab program is not a substitute for a real lab, but as a complement for learning of the material that is hard to do in a real laboratory, such as the practicum invertebrates.Keywords: invertebrates, virtual lab, scientific attitudes